Property and Trust Law: Singapore - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2018)
This book is written as a general introduction to the laws of property and trusts in Singapore. The topics are examined against the country’s history, societal conditions and policies to highlight trends and aspects of property and trust laws that are unique to Singapore. Originally written with our students in mind, we have attempted to strike a good balance between accessibility and depth. With an emphasis on the practical application of the law, the legal principles are discussed by reference to the facts of decided cases and real-life examples. By also weighing in on controversial aspects of the law, we hope that this book will appeal not only to students but also to scholars and practitioners.